(untitled) (Asian Journal of Social Science Studies, 2022)
Zhanli Kam village in the Qiandongnan Region of Guizhou Province is known as ‘the first village in China for family planning.’ Geographic isolation and limited resources have led the Zhanli people to coordinate population and resources through autonomous family planning. There is a magical local herb called ‘flower changing herb’ that can control the sex of the foetus. Thus, every family in Zhanli has only one son and one daughter. People and the environment are not simply in a constraining relationship but are organically linked. The key lies in the moderating role of culture. This thesis aims to interpret the symbiotic concept behind the usage of the herb. Based on ethnographic research conducted in Zhanli, this thesis will explain how the symbiotic concept guides the Zhanli people’s behaviours by analysing the relationship between humans and nature, individuals and the community. Besides, this thesis will also figure out how Zhanli encounters the outside world on the impact of the penetration of urban culture and the government’s poverty reduction programme. Guided by the symbiotic concept, the Zhanli people constantly negotiate with their environment to create a cultural landscape that subverts the dichotomy between human society and the natural environment.